MENUMBUHKAN JIWA WIRAUSAHA UNTUK MENINGKATKAN KEMANDIRIAN IBU-IBU PKK DESA ARGOSARI - Bunyamin Bunyamin; Siti Munfaqiroh; Lailatus Sa’adah; Widanarni Pudjiastuti; Lindananty Lindananty; Dwi Danesty D.; Marli Marli; Rina Rahmawati; Didik Priyo S.; Zainul Arifin; Yupono Bagyo; Wiyarni Wiyarni; Eko Sudjawoto (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Argosari Village is a village that is very active in making efforts to improve the welfare and economy of its citizens by providing various knowledge and skills, especially for PKK and Karang Taruna women. The results of observations and preliminary interviews showed that most of the people of Argosari village did not know that entrepreneurship is a person's ability to create jobs for himself and others. This service aims to help the community to develop self-confidence, as well as a need for achievement so that a high work ethic arises, and is happy to work hard. The method used is to socialize the program, provide materials, training and mentoring. The result of this service is the increase in participants' skills in sewing bags and masks as well as assembling mask connector materials.